Stable and Unstable Chromosome Aberrations Measured after Occupational Exposure to Ionizing Radiation and Ultrasound - Fučić, Aleksandra (Croatian Medical Schools, 2007)
AIM: To evaluate chromosome aberration and fluorescent in situ hybridization (FISH) assays as a method to estimate of health risk, we monitored 9 male subjects occupationally exposed to low doses of both ionizing radiation and ultrasound during a period of over 3 years. METHODS: Sampling was performed at 6-month intervals during a three-year period. First we used conventional chromosomal aberrations analysis. When the aberration frequency for a particular subject reached the background, we measured translocations in the final sample, using fluorescence in situ hybridization. Chromosome painting probes for chromosomes 1, 2, and 4 were used simultaneously. RESULTS: Dicentric and ring chromosomes were eliminated within a year. Translocations persisted and deviated from control values in all examinees. Translocations were detected long after unstable aberrations decreased to the background level. CONCLUSION: Fluorescence in situ hybridization-based translocation detection was a reliable method for monitoring chronic occupational clastogen exposure. Chromosome aberration assay correlated with translocation frequency. Stable chromosomal aberrations reflected cumulative genome damage during job exposure.